Two-Eyed Seeing into shipwrecks: maritime microscopy in the South Carolina Lowcountry - Rich, Sara A.; Raimondi, Kayla; Herness, Hannah (Frontiers in Environmental Archaeology, 2025)
By enhancing methods for how archaeology can contribute to the study of multi-species shipwrecks (or shipwreck ecology), this paper reconsiders the function of non-functioning ships and boats from anti-colonial and Native American perspectives. In partnership with the Waccamaw Indian People and the Indigenize SC Education Task Force, wood samples from several submerged wreck sites in a blackwater tidal river in the Lowcountry of South Carolina (USA) were analyzed for their archaeological potentials and for their potential to disclose the performance of individual sites within the underwater ecosystems of which they are a part. In turn, this information offers the opportunity to inform the public about the ecological roles of wreckage, thereby expanding the typical archaeological research questions into ones pertaining to sovereignty: namely, Indigenous and water. Following a thorough review of relevant literature and theory, the results of microscopic analyses of submerged sites are presented, along with an introduction to the interactive museum exhibit derived from the data and the questions they raise. In these ways, the paper moves between archaeological theory, scientific methodology, and the practice of public pedagogy.